Rural co-working: New network spaces and new opportunities for a smart countryside. (January 2023) - Bosworth, Gary; Whalley, Jason; Fuzi, Anita; Merrell, Ian; Chapman, Polly; Russell, Emma
Abstract: Coworking has been a largely urban phenomenon although new initiatives are emerging in rural areas. Rural coworking is partly a response to the growing need for ICT, which is unevenly provided across rural areas, and partly to the social needs of freelancers and home-workers. By combining technological and social functions, coworking spaces can play key roles in the progress of a Smart Countryside, supporting digital, knowledge-based and creative entrepreneurs within rural places, thus reducing the need for extensive commuting and out-migration, particularly among younger and higher-skilled workers. As working practices evolve in the aftermath of Covid-19, these new physical spaces are expected to facilitate new network connections. Castells' Network Society provides a valuable lens through which to investigate how coworking founders and managers promote a mix of internal and external networks that might create new, and superior, entrepreneurial opportunities. The research highlights strategies to promote collaboration as well as methods of adapting to meet new demands from rural workers in a range of rural settings. As an array of different rural coworking models evolve, we also reflect on the importance of inclusivity and identity in determining their relationship with other actors in the local economy. Highlights: Castells' Network Society is applied to understand changes in the rural economy. Distinctive success factors for rural co-working spaces are identified. Rural co-working spaces create and sustain new business networks. Co-working embodies a 'smart countryside', mixing social and technological elements.